Co-ownership of apartment owners with regard to the land on which the building is built - Cvetić, Radenka; Midorović, Sloboda D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The focus of this paper rests on the right of apartment owners on the land on which the building was built and the land that serves to its regular use. The paper aims at identifying the type of that right; over which land that right streches, and, eventually, which legal rules are relevant for that right. The answers to these questions require a systematic interpretation of solutions from several lega sources, most notably the Law on Foundations of Property Law Relations, the Law on Housing and Maintenance of Apartment Buildings and the Law on Planning and Construction. With regard to the legal regime of that right, the paper concludes that special rules establish numerous deviations from the general regime that, in the absence of a special set of rules, would otherwise be applicable to it. Deviations were detected with regard to the: 1) authority to dispose of the share in the ownership right over that land; 2) management of that land; 3) dissolution of the co-ownership community that exists among apartment owners in relation to that land, and 4) covering of costs incurred by the use and maintenance of that land. Theoretical considerations have been supplemented by an analysis of a case from a recent domestic jurisprudence that underlines a practical dimension of the elaborated subject matter.
Keywords: apartment ownership, co-ownership, land for the regular use of the building, special co-ownership regime